INTERNATIONALIZATION OF TOURISM SPECIALISTS’ VOCATIONAL TRAINING IN TURKEY AND UKRAINE - Malyshevа, Makhyrа (Studies in Comparative Education, 2017)
The article highlights the urgency of internationalization processes in vocational training of tourism specialists in Turkey and Ukraine. The structure of national education systems and the peculiarities of tourism specialists’ vocational training in vocational education institutions of Turkey and Ukraine have been presented. It has been revealed that the Turkish national education system is divided into formal and informal. It has been pointed out that Turkish schools for commerce and tourism are similar to the Ukrainian higher vocational schools of tourism. It has been indicated that vocational training of tourism and hospitality specialists in Ukraine is carried out in vocational schools, technical schools, colleges, higher education institutions. It has been revealed that on the way to international integration and promotion of a positive image of tourism industry in the world, both Turkey and Ukraine have faced the need to improve the system of vocational training of tourism and hospitality specialists on the basis of studying inter-nationalization processes and their influence on development of the national educa-tion systems. The international documents on the tourism development regulation in Turkey have been analyzed; the intergovernmental agreements of Ukraine aimed at establishing effective cooperation in the field of vocational training of tourism specialists have been considered. The perspective tasks related to approximation of the quality of tourism specialists’ vocational training in Ukraine to the inter-national requirements of the tourism industry have been outlined. They are as follows: to achieve correspondence of relevant syllabi and training programmes to international standards; to ensure multidisciplinarity of syllabi and training pro-grammes, integration of international elements into curricula; to form individual mobility of the subjects of learning; to promote institutional partnership: to involve domestic (national) and foreign (international) investments in order to create an effective, cross-border system of vocational training of future tourism specialists.